2020
DOI: 10.1017/pasa.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Resistive accretion flows around a Kerr black hole

Abstract: In this paper, we present the stationary axisymmetric configuration of a resistive magnetised thick accretion disc in the vicinity of external gravity and intrinsic dipolar magnetic field of a slowly rotating black hole. The plasma is described by the equations of fully general relativistic magnetohydrodynamics (MHD) along with the Ohm's law and in the absence of the effects of radiation fields. We try to solve these two-dimensional MHD equations analytically as much as possible. However, we sometimes inevitab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Numerical simulations have shown that the resistive dissipation can affect the growth rate and the saturation level of MRI (Fleming, Stone, & Hawley 2000;Sano & Stone 2002a;2002b;Masada & Sano 2008;Simon & Hawley 2009;Bai & Stone 2013;Rodgers-Lee, Ray, & Downes 2016) and also the rate of angular momentum transport (Ziegler & Rüdiger 2001;Fromang et al 2007;Longaretti & Lesur 2010) in these systems. The importance of resistivity in other systems like the discs around Kerr black holes (Kudoh & Kaburaki 1996;Qian et al 2017;Qian et al 2018;Shaghaghian 2020), and even Sgr A * at the Galactic Center (e.g. Melia & Kowalenko 2001), has also been recognised.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations have shown that the resistive dissipation can affect the growth rate and the saturation level of MRI (Fleming, Stone, & Hawley 2000;Sano & Stone 2002a;2002b;Masada & Sano 2008;Simon & Hawley 2009;Bai & Stone 2013;Rodgers-Lee, Ray, & Downes 2016) and also the rate of angular momentum transport (Ziegler & Rüdiger 2001;Fromang et al 2007;Longaretti & Lesur 2010) in these systems. The importance of resistivity in other systems like the discs around Kerr black holes (Kudoh & Kaburaki 1996;Qian et al 2017;Qian et al 2018;Shaghaghian 2020), and even Sgr A * at the Galactic Center (e.g. Melia & Kowalenko 2001), has also been recognised.…”
Section: Introductionmentioning
confidence: 99%